Evidence of the impacts of emerging shark tourism in the Mediterranean. (1st August 2019) - Zemah Shamir, Ziv; Zemah Shamir, Shiri; Becker, Nir; Scheinin, Aviad; Tchernov, Dan
Abstract: Shark tourism is a new concept that has not yet been recognized in Israel. While the principles and regulation of shark tourism in particular and wildlife tourism in general are developing rapidly worldwide, in Israel we are only at the very beginning of this process. The aggregations of sharks near the power plant in Hadera (in the middle-northern part of the Israeli coast) are a source of interest and attraction for many people, including swimmers, divers, and kayakers. The desire of tourists, and therefore of local businesses as well, to take part in this amazing and profitable phenomenon poses certain risks, in view of the lack of regulation in the area. In this study we analyse the ecological-socioeconomic consequences of shark tourism as well as the risks of visitor pressure for the environment. Our observations suggest that human divers might disturb the sharks and influence behavioral changes. We call on decision makers to regulate the area have least ecological damage so that the sharks can live with minimum disturbance while allowing some reasonable amount of wildlife tourism. Highlights: There is evidence that the mere presence of human observers can affect shark behaviour. Changes in shark aggregations also affect the tourists who come to see the sharks, shifting the costs and benefits of tourism. We recommend developing management tools to improve the cost–benefit ratio for all stakeholders in the area, including the sharks. We recommend that the Israel Nature and Parks Authority control this area as a dynamic marine reserve during shark season (November through May). We recommend: no more than eight pairs of divers in the water at the same time, and divers must stay at least 3 m from the sharks.